The fashion design course : principles, practice and techniques: the ultimate guide for the aspiring fashion designer - Faerm, Steven (Thames and Hudson, 2022)
"A fully updated, third edition of this essential practical foundation course in fashion design. Becoming a successful fashion designer involves understanding a wide variety of core principles. This foundation course is an ideal introduction for students, dressmakers and anyone interested in the creative side of fashion. Step-by-step tutorials, practical exercises and inspirational interviews with industry professionals teach you how to create your own unique fashion design collections. Design schools around the world are now emphasising design thinking and conceptualisation more than just mere skill building. Packed with scores of new images, this new and fully updated edition provides students with more diverse methods of creating fashion, including digital design iteration and final projects, fabric design development, 3D 'sketching' on the dress form, paper collage design techniques and much more. This book concludes with practical advice for anyone considering a career in fashion, offering ideas on building a portfolio, preparing for interviews and continuing on a path to a professional career"--Publisher's description.